Pengembangan Aplikasi Laundry Salsabila Menggunakan Iterative Model - Irman Gantira; Rendi Sabillillah; Ramdoni Ramdoni; Muhammad Yusup; Yulianti Yulianti; Sri Mulyati (Teknik Informatika Universitas Pamulang, 2022)
Laundry service is a highly anticipated demand of the public, washing services are known as laundry services, which are a service to reduce the burden of daily household activities. with the large need and demand for washing services or laundry services at this time, it is possible for washing service owners to be able to maximize their business by conducting transactions with consumers, recording transaction results along with monthly business reports requires a lot of energy and time. various activities and businesses including laundry services allow laundry service businesses to have an effective time, efficient business with the convenience of computerized applications such as the Salsabila laundry service application, applications that are made to make it easy to transact, digitally collect consumer data, book business activities every month with relatively fast and efficient time. The methodology applied in building this application uses an SLDC system based on the iterative model method. This application development is made in PHP and uses MySQL for the database. With this application, it is easier to input data, create structured trading notes and generate accurate reports.